2020
DOI: 10.1371/journal.pone.0231868
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between executive functions and fluid intelligence in multiple sclerosis

Abstract: Background & objective Deficits in cognitive functions dependent upon the integrity of the prefrontal cortex have been described in Multiple Sclerosis (MS). In a series of studies we have shown that fluid intelligence (g) is a substantial contributor to frontal deficits and that, for some classical "executive" tasks, frontal deficits were entirely explained by g. However, for another group of frontal tasks deficits remained once g was introduced as a covariate. This second set of tests included multitasking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Due to the substantial heterogeneity of assessments that were used to quantify cognitive impairment, fatigue and depression, as well as insufficient data, we were not able to integrate the variable cognition, as well as depression for cToM(faux-pas) and fatigue for cTom(videos). In the analysis on cToM(faux-pas), that included three studies 27 , 29 , 37 , R 2 was 100% (meaning 100% of the difference in true effect sizes can be explained by the predictor fatigue), and the intercept as well as the predictor fatigue were significant (intercept: − 1.73 ( p < 0.001), fatigue: 0.02 ( p < 0.05)). This means that performance on cTom (faux-pas) decreased with higher fatigue levels.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the substantial heterogeneity of assessments that were used to quantify cognitive impairment, fatigue and depression, as well as insufficient data, we were not able to integrate the variable cognition, as well as depression for cToM(faux-pas) and fatigue for cTom(videos). In the analysis on cToM(faux-pas), that included three studies 27 , 29 , 37 , R 2 was 100% (meaning 100% of the difference in true effect sizes can be explained by the predictor fatigue), and the intercept as well as the predictor fatigue were significant (intercept: − 1.73 ( p < 0.001), fatigue: 0.02 ( p < 0.05)). This means that performance on cTom (faux-pas) decreased with higher fatigue levels.…”
Section: Resultsmentioning
confidence: 99%
“…This latter finding has also been reported in MS and could play a role in altering executive deficits. 49…”
Section: Discussionmentioning
confidence: 99%
“…This latter finding has also been reported in MS and could play a role in altering executive deficits. 49 To our knowledge, only one study has investigated functional connectivity in RIS patients. 17 In that study, 17 no differences in functional brain connectivity were found between RIS subjects and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that EF deficits can be largely explained by a loss of general intelligence. 40 In fact, both cognitive functions are supported by the prefrontal cortex (PFC) and the EF deficits have been found to be related to lesions of the frontosubcortical tracts.…”
Section: Executive Functionsmentioning
confidence: 99%